Exact Solutions of the Time Fractional BBM-Burger Equation by Novel (G′/G)-Expansion Method - Muhammad Shakeel; Qazi Mahmood Ul-Hassan; Jamshad Ahmad; Tauseef Naqvi (Advances in Mathematical Physics)
The fractional derivatives are used in the sense modified Riemann-Liouville to obtain exact solutions for BBM-Burger equation of fractional order. This equation can be converted into an ordinary differential equation by using a persistent fractional complex transform and, as a result, hyperbolic function solutions, trigonometric function solutions, and rational solutions are attained. The performance of the method is reliable, useful, and gives newer general exact solutions with more free parameters than the existing methods. Numerical results coupled with the graphical representation completely reveal the trustworthiness of the method.